NÃVEIS DE AÇUCARES E ATIVIDADE DE INVERTASES EM CANA-DE-AÇÚCAR (Saccharum officinalis SPP.) I. CULTIVARES NA 56-79 E CB41-76 - Vieira, Irenice M. S.; Oliveira, Enio T. de; Gallo, Luiz A.; Batista, Telma F. C.; Rodrigues, Rosana C.; Crocomo, Otto J. (REVISTA DE AGRICULTURA, 2015)
NÃVEIS DE AÇUCARES E ATIVIDADE DE INVERTASES EM CANA-DE-AÇÚCAR (Saccharum officinalis SPP.) I. CULTIVARES NA 56-79 E CB41-76